2014
DOI: 10.2215/cjn.04960513
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stones and Cardiovascular Events

Abstract: Background and objectives Kidney stones are common in general clinical practice, and their prevalence is increasing. Kidney stone formers often have risk factors associated with atherosclerosis, but it is uncertain whether having a kidney stone is associated with higher risk of cardiovascular events. This study sought to assess the association between one or more kidney stones and the subsequent risk of cardiovascular events.Design, setting, participants, & measurements Cohort study of 3,195,452 people aged$18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 25 publications
(31 reference statements)
7
107
3
3
Order By: Relevance
“…This is in accordance with epidemiologic studies indicating that idiopathic calcium renal stone formers, the great majority of renal stone patients, are at increased risk of cardiovascular events. The data also suggest that results obtained by previous cohort studies disclosing an association with increased carotid intima-media thickness, and CV endpoints, respectively [2,13,14,19], are probably explained by the higher CV risk imparted by idiopathic calcium stones rather than by other special kind of stone formers, for example the urate stone patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is in accordance with epidemiologic studies indicating that idiopathic calcium renal stone formers, the great majority of renal stone patients, are at increased risk of cardiovascular events. The data also suggest that results obtained by previous cohort studies disclosing an association with increased carotid intima-media thickness, and CV endpoints, respectively [2,13,14,19], are probably explained by the higher CV risk imparted by idiopathic calcium stones rather than by other special kind of stone formers, for example the urate stone patients.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, three prospective studies have confirmed that incident stone formers have a 20-60 % higher risk of having incident CV episodes [2,13,14]. However, the epidemiological design of those studies had precluded the possibility to ascertain whether the risk is associated with a specific phenotype of renal stone disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 45,748 men and 196,357 women from the United States, Ferraro et al demonstrated that among women, those with a reported history of kidney stones had a significantly higher adjusted risk of CVD than those without a history of kidney stones (4). Finally, in a recent cohort study of 3,195,452 people, the occurrence of a kidney stone was associated with a higher risk of acute MI, percutaneous transluminal coronary angioplasty/coronary artery bypass grafting, and stroke (16).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have suggested an association between urolithiasis, adverse cardiovascular events, and vascular calcification risk factors such as obesity and diabetes mellitus [14]. Although risk factors for urinary stone disease are recognized, only the mere association between the two is known, not causation.…”
mentioning
confidence: 99%